PENERAPAN REKAYASA NILAI PADA PROYEK PEMBANGUNAN GEDUNG SEKOLAH (STUDI KASUS PEMBANGUNAN GEDUNG SEKOLAH SANUR INDEPENDENT SCHOOL) - Martha Jaya, Nyoman; Agung Yana, Anak Agung Gde; Erick Triswandana, I Wayan Gde (JURNAL SPEKTRAN, 2019)
THE IMPLEMENTATION OF VALUE ENGINEERING ON SCHOOL BUILDING CONSTRUCTION PROJECT (CASE OF STUDY SANUR INDEPENDENT SCHOOL) ABSTRACT In a construction project, the cost is one of the factors that determine the sustainability of the project, especially in the case of study school building project at Sanur Independent School. Because of that, the austerity measures undertaken to produce an economical construction project. The selection of materials and construction methods can precisely determine the amount of savings to be gained in the implementation of the construction project, wherein the choice of materials and alternative methods will not necessarily reduce nor change the value of the function, quality and architectural value of the project itself. Therefore there is a need for job costing analysis to control these aspects. One of the methods that used for cost efficiency in a construction project especially on the building construction is Value Engineering Method that is a systematic way of defining the value of a subject to its function so that an innovative and structured approach can be adopted with the aim of reducing unnecessary costs. By using this method can obtained two alternative combinations of designs such as , the best combination of alternative designs and the cheapest combination of alternative design, and based by the result of the researched, by using a combination of the best alternative design on this construction project wherein the initial BoQ have a value of Rp 2,003,372,657.68 obtained savings of Rp 36.492.428,34 atau 1,82 %. While using a combination of the cheapest alternative designs obtained savings of Rp 248,161,362.38 or 12.39 %.